2019
DOI: 10.3390/batteries5010018
|View full text |Cite
|
Sign up to set email alerts
|

Discharge by Short Circuit Currents of Parallel-Connected Lithium-Ion Cells in Thermal Propagation

Abstract: The increasing need for high capacity batteries in plug-in hybrids and all-electric vehicles gives rise to the question of whether these batteries should be equipped with a few large capacity cells or rather many low capacity cells in parallel. This article demonstrates the possible benefits of smaller cells connected in parallel because of discharge effects. Measurements have been conducted proving the beneficial influence of a lower SoC on the thermal runaway behaviour of lithium-ion cells.A second test seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Mao et al [26] revealed the thermal stability and component heat contribution ratio of overcharged lithium-ion batteries during TR and discovered that increasing SOC could decrease the activation energy of exothermic side reactions. Koch et al [27] investigated the TR reaction in pouch batteries at different SOCs, which not only revealed the amount of energy released during a TR reaction but also uncovered that the change in mass (mass lost) after TR is less in batteries with a low SOC than at a higher SOC. Chen et al [28] studied the TR behaviors of nickel-rich li-ion batteries and revealed the TR characteristics under different SOCs.…”
Section: Introductionmentioning
confidence: 99%
“…Mao et al [26] revealed the thermal stability and component heat contribution ratio of overcharged lithium-ion batteries during TR and discovered that increasing SOC could decrease the activation energy of exothermic side reactions. Koch et al [27] investigated the TR reaction in pouch batteries at different SOCs, which not only revealed the amount of energy released during a TR reaction but also uncovered that the change in mass (mass lost) after TR is less in batteries with a low SOC than at a higher SOC. Chen et al [28] studied the TR behaviors of nickel-rich li-ion batteries and revealed the TR characteristics under different SOCs.…”
Section: Introductionmentioning
confidence: 99%
“…From the results of the research by Lamb et al on 18 650 cylindrical cells and small pouch cells, 30 it can be seen that parallel connection does accelerate or promote the occurrence of thermal propagation. Koch et al 31 showed that the lower the state‐of‐charge (SoC) of the battery, the higher the initial temperature during thermal runaway, and the smaller the mass loss caused by thermal runaway (it is generally considered that the lower the severity of the thermal runaway, the smaller the released energy). Gao et al 32 conducted experiments and simulation studies on prismatic cells, proposed a method to study the Joule heating effect generated by the discharge during thermal runaway in parallel circuits, and further proposed a simulation study by establishing an equivalent circuit model for quantification.…”
Section: Introductionmentioning
confidence: 99%
“…There is a variety of articles focusing on modeling [11][12][13][14][15], aging [16][17][18], safety [19][20][21], state estimation [22,23] and measurement [24][25][26] of parallel-connected cells. Mostly qualitative effects like OCV [27], SoC [13], temperature [13,26,28,29] and current differences [13] are demonstrated but quantitative relationships are missing, especially with regard to the thermal connection of the cells to neighboring cells and cooling.…”
Section: Introductionmentioning
confidence: 99%